PENGARUH PROMOSI DAN HARGA TANAMAN HIAS TERHADAP KEPUTUSAN PEMBELIAN PADA AROY NURSERY DI TANGERANG - Juwitha Permata Sari; Agus Sudarsono (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of promotions and prices on purchasing decisions at Aroy Nursery in Tangerang, both partially and simultaneously. The research method used is a quantitative method with a descriptive approach. The sampling technique used was incidental sampling, namely using a total consumer population of 1,582 with a sample of 94 respondents. The data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis testing. The research results of promotion and price partially have a positive and insignificant effect on purchasing decisions at Aroy Nursery as shown by the multiple linear regression equation Y = 0.476 + 0.598X1 + 0.407X2. This is proven by the results of the promotional hypothesis test, which obtained a value of tcount 13,155 > ttable 1.986 and was strengthened by the value ρ value < Sig.0.05 or a significance value < 0.05 (0.000 < 0.05). (0.000 < 0.05). This is proven by the results of simultaneous hypothesis testing obtained by the Fcount value (168,722 > Ftable 3.10) and reinforced by the significance value < 0.00 (0.000 < 0.05). shows that the correlation coefficient is at the level of 0.800 - 1.000, so the level of correlation between the promotion and price variables on purchasing decisions is interpreted as very strong and the value of the coefficient of determination is 0.788 or 78.8% while the remaining 21.1% is influenced by other factors. This means that it is proven that there is a simultaneous insignificant influence between promotion (X1) price (X2) on purchasing decisions (Y). Thus, H03 is rejected and Ha3 is accepted.